Reproducibility of the external surface position in left‐breast DIBH radiotherapy with spirometer‐based monitoring. (4th January 2014) - Fassi, Aurora; Ivaldi, Giovanni B.; Meaglia, Ilaria; Porcu, Patrizia; de Fatis, Paola Tabarelli; Liotta, Marco; Riboldi, Marco; Baroni, Guido
Abstract : Deep inspiration breath hold (DIBH) in left‐sided breast cancer radiotherapy treatments allows for a reduction in cardiac and pulmonary doses without compromising target coverage. The selection of the most appropriate technology for DIBH monitoring is a crucial issue. We evaluated the stability and reproducibility of DIBHs controlled by a spirometric device, by assessing the variability of the external surface position within a single DIBH (intra‐DIBH) and between DIBHs performed in the same treatment session (intrafraction) or in different sessions (interfraction). The study included seven left‐breast cancer patients treated with spirometer‐based DIBH radiotherapy. Infrared optical tracking was used to record the 3D coordinates of seven to eleven passive markers placed on the patient's thoraco‐abdominal surface during 29‐43 DIBHs performed in six to eight treatment sessions. The obtained results showed displacements of the external surface between different sessions up to 6.3 mm along a single direction, even at constant inspired volumes. The median value of the interfraction variability in the position of breast passive markers was 2.9 mm (range 1.9‐4.8 mm) in the latero‐lateral direction, 3.6 mm (range 2.2‐4.6 mm) in the antero‐posterior direction, and 4.3 mm (range 2.8‐6.2 mm) in the cranio‐caudal direction. There were no significant dose distribution variations for target and organs at risk with respect to the treatment plan, confirming the adequacy of the applied clinical margins (15 mm) to compensate for the measured setup uncertainties. This study demonstrates that spirometer‐based control does not guarantee a stable and reproducible position of the external surface in left‐breast DIBH radiotherapy, suggesting the need for more robust DIBH monitoring techniques when reduced margins and setup uncertainties are required for improving normal tissue sparing and decreasing cardiac and pulmonary toxicity. PACS number: 87.55.Km